Survey of athletic injuries for exercise science - Diaz, Linda Gazzillo. (Jones & Bartlett Learning, 2014)
Written for students within Exercises Science and Exercise Physiology, Survey of Athletic Injuries for Exercise Science clearly outlines traditional prevention and care of athletic injuries for those who do not have an athletic training background. It addresses the role that professionals in exercise science, exercise physiology, and other health-related fields play in the treatment of injuries and illnesses in the physically active population. The text focuses on each body segment along with other information that impacts the physically active, such as ergogenic aids, supplements, nutrition, and exercise prescription. Throughout the text case studies and realistic situation boxes discusses interesting cases from the field. Provides a necessary resource on athletic injury and prevention for the non-athletic trainer. Clearly defined chapter objectives identify critical information for students. Critical thinking questions ask students to examine and reason through a variety of scenarios. Case Studies throughout analyze and explore real-world situations. -